Combinatory effect of BRCA1 and HERC2 expression on outcome in advanced non-small-cell lung cancer. Issue 1 (December 2016) - Bonanno, Laura; Costa, Carlota; Majem, Margarita; Sanchez, Jose-Javier; Rodriguez, Ignacio; Gimenez-Capitan, Ana; Molina-Vila, Miquel; Vergnenegre, Alain; Massuti, Bartomeu; Favaretto, Adolfo; Rugge, Massimo; Pallares, Cinta; et al.
Abstract Background BRCA1 is a main component of homologous recombination and induces resistance to platinum in preclinical models. It has been studied as a potential predictive marker in lung cancer. Several proteins modulate the function of BRCA1. The E3 ubiquitin ligase HERC2 facilitates the assembly of the RNF8-UBC13 complex to recruit BRCA1 to DNA damage sites. The combined analysis of multiple components of the pathway leading to the recruitment of BRCA1 at DNA damage sites has the potentiality to improve the BRCA1 predictive model. Methods We retrospectively analyzed 71 paraffin-embedded tumor samples from advanced non-small-cell lung cancer patients treated with first-line platinum based chemotherapy and measured the mRNA expression levels ofBRCA1, RNF8, UBC13 andHERC2 using real-time PCR. The mRNA expression was categorized using median value as cut-off point. Results The median progression-free survival of all 71 patients was 7.2 months whereas the median overall survival of the study population was 10.7 months. Among patients with lowBRCA1 expression, the median PFS was 7.4 months in the presence of lowHERC2 levels and 5.9 months for patients expressing highHERC2 levels (p  = 0.01). The median OS was 15.3 months for patients expressing low levels of both genes and 7.4 months for those with low BRCA1 but high HERC2 (p  = 0.008). The multivariate analysis showed that among patients with Eastern Cooperative Oncology Group performance status 0–1, the combined low expression of bothBRCA1 andHERC2 clearly reduced the risk of progression (p  = 0.03) and of death (p  = 0.004). Conclusions These findings confirm the potentiality of integrated DNA repair components analysis in predicting the sensitivity to platinum in lung cancer. The study indicates a predictive role for HERC2 mRNA expression and paves the way for further refinement of the BRCA1 predictive model.